A rare case of thymus lipofbroadenoma - A. V. Shilov; A. M. Avdalyan; A. S. Shargin; A. V. Levitsky; D. N. Protsenko (Сибирский онкологический журнал, 2023)
Purpose of the study: differential diagnosis of tumors arising from the mediastinum, as well as the analysis of the biological potential of the tumor, taking into account the relatively low incidence of these tumors among the population.Material and Methods. Macroscopic and microscopic examinations of the surgical specimen were performed using routine H&E staining. Immunohistochemical staining of paraffin-embedded tissue sections was performed using a Roche Ventana BenchMark Ultra system. The results obtained were evaluated taking into account the available literature data published on this nosology.Description. We present a rare case of a benign neoplasm of the thymus, lipofibroadenoma (LFA), which was localized in the left pleural cavity and originated from the anterior mediastinum with partial compression of the lower lobe of the left lung in a 59-year-old man. The tumor was revealed during a routine medical examination. The patient underwent left-sided thoracotomy with complete excision of the tumor and anterior mediastinal lymph node dissection. Macroscopic examination reveled that the tumor was predominantly composed of adipose tissue with fibrous layers. Histological examination showed a tumor composed of mature adipocytes of various sizes, among which remnants of the thymus with Hassal’s bodies and small number of lymphocytes and calcifications were found. Areas of fibrous stroma predominated over narrow strands of anastomosing epithelial cells with clear nuclei. Epitheliocytes formed slit-like structures infiltrated with lymphocytes, resembling the structure of breast fibroadenoma. Immunohistochemical examination revealed that epithelial cells were positive for PanKeratin and CK19, lymphocytes were positive for CD3 and CD20, and thymic cells expressed TdT. In this case, the neoplasm was almost asymptomatic, in contrast to previously published observations, which described an association with erythrocyte aplasia.Conclusion. Considering the clinical, histological and immunohistochemical data, it was feasible to make a differential diagnosis of the neoplasm and determine the histological type of the tumor as lipofibroadenoma.